A high-osmotic composite dressing containing a heterojunction nano-enzyme and a preparation method and application thereof
Patent Information
- Application Number
- CN202611517076.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-29
- Publication Date
- 2026-11-03
AI Technical Summary
[0008]针对现有技术的不足,本发明提供了一种含异质结纳米酶的高渗性复合敷料及制备方法与应用,解决了复杂渗出环境下功能组分难以稳定负载、易发生突释及疗效难以持续等问题
[0026](1)本发明将具有SOD(超氧化物歧化酶)和CAT(过氧化氢酶)活性的纳米酶与高渗性敷料体系相结合,并在纳米酶上负载功能组分(维生素D3和甘氨酸),再经透明质酸(HA)表面修饰,构建了一种适用于糖尿病足慢性创面治疗的高渗性复合敷料。所制备的纳米酶具有较高的比表面积和较丰富的孔道结构,有利于维生素D3和甘氨酸的负载。同时,结合透明质酸表面修饰作用,可提高维生素D3在创面复杂渗出环境中的释放稳定性,从而为局部持续作用提供基础。
Smart Images

Figure CN123024176A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of inorganic materials technology, specifically to a hyperpermeable composite dressing containing heterojunction nanozymes, its preparation method, and its application. Background Technology
[0002] Diabetic foot chronic wounds (DFU) are a common and serious lower limb complication in diabetic patients, and one of the most challenging and difficult-to-heal wounds in orthopedic clinics. Due to the long-term weight-bearing on the foot, coupled with peripheral neuropathy, impaired local blood circulation, and reduced tissue repair capacity, the wounds are prone to repeated damage and prolonged non-healing. As infection and tissue necrosis worsen, the lesions can further affect deep soft tissues, joints, and even bone, increasing the risk of deep infection, osteomyelitis, and amputation. Therefore, effective management of diabetic foot wounds is crucial for maintaining foot function and improving limb salvage rates. Limb preservation is a significant clinical issue in orthopedic limb salvage therapy and chronic wound management.
[0003] Currently, orthopedic clinics typically employ a comprehensive approach including debridement, decompression, infection control, negative pressure therapy, and functional dressings. However, post-debridement wounds often exhibit persistent exudation, local inflammation, increased oxidative stress, and a risk of recurrent infection. Ordinary dressings primarily serve to cover and absorb fluid, but their ability to actively regulate the complex wound microenvironment is limited, making it difficult to meet the long-term treatment needs of diabetic foot.
[0004] In dressing therapy, hypertonic dressings absorb exudate through osmotic pressure gradients and reduce local water activity, thereby inhibiting microbial proliferation and alleviating wound edge edema, and playing a positive role in improving the wound microenvironment. However, current technologies, relying solely on a hypertonic environment, are insufficient to address key issues such as persistent inflammation and increased oxidative stress in chronic diabetic foot wounds. Therefore, it is necessary to further introduce functional components into hypertonic dressing systems that can regulate oxidative stress and alleviate inflammatory responses, while also helping to inhibit infection progression, to form a multi-mechanism synergistic intervention.
[0005] Nanozymes are a class of nanomaterials with enzyme-like catalytic activity that can mimic antioxidant enzymes such as superoxide dismutase (SOD) and catalase (CAT) to scavenge reactive oxygen species (ROS). In chronic diabetic foot wounds, long-term elevated ROS levels exacerbate inflammation and hinder granulation tissue formation. SOD / CAT-like nanozymes hold promise for promoting repair by reducing oxidative stress and alleviating inflammation. Furthermore, their good stability, ease of loading, and formulation make them suitable for integration with dressing systems to construct local treatment platforms.
[0006] However, existing nanozymes still have limitations in the treatment of chronic diabetic foot wounds. On the one hand, some nanozymes have low or singular enzyme-like catalytic activity, making it difficult to effectively remove the various reactive oxygen species (ROS) continuously generated in the microenvironment of chronic diabetic foot wounds. Furthermore, under conditions of complex exudation, high glucose inflammation, and local pH changes, the catalytic activity of nanozymes is prone to attenuation, thus affecting their efficacy in regulating oxidative stress and alleviating inflammatory responses. On the other hand, existing nanozymes, when used as drug carriers, suffer from limited drug loading capacity, unstable drug binding, and insufficient release regulation. This can easily lead to premature drug leakage, early burst release, and insufficient late release in the wound's exudative environment, making it difficult to meet the needs of long-term, continuous treatment of chronic diabetic foot wounds.
[0007] Based on the above problems, there is an urgent need to develop a composite dressing adapted to the complex microenvironment of chronic diabetic foot wounds and possessing synergistic effects through multiple mechanisms, as well as its preparation method. This composite dressing preferentially combines nanozymes with SOD / CAT activity with a hypertonic dressing, enabling exudation management and auxiliary bacterial control within the hypertonic environment. Simultaneously, the nanozyme catalyzes the removal of excess ROS to alleviate oxidative stress and inflammatory responses. Furthermore, it utilizes the carrier capacity of the nanozyme to achieve stable loading and sustained release of functional components, thereby achieving a more durable, stable, and predictable therapeutic effect in the treatment of chronic diabetic foot wounds. Summary of the Invention
[0008] To address the shortcomings of existing technologies, this invention provides a hyperpermeable composite dressing containing heterojunction nanozymes, its preparation method, and its application, solving problems such as the difficulty in stably loading functional components, the susceptibility to burst release, and the difficulty in maintaining therapeutic efficacy under complex exudative environments. This method first constructs a dressing with a large specific surface area (176.3 m²). 2 A nanozyme carrier with a rich porous structure ( / g) was used to efficiently load various functional components onto its pores or surface. Surface modification with hyaluronic acid (HA) was then performed to enhance interfacial stability and diffusion barrier capabilities, ultimately forming a hypertonic dressing. The resulting dressing enables the slow and sustained release of functional components, effectively reducing the risk of burst release. Simultaneously, the nanozyme scavenges excess ROS and synergizes with the loaded functional components in anti-inflammatory, antibacterial, moisturizing, and structural stabilizing effects, promoting wound microenvironment reconstruction and tissue repair. This leads to more stable and durable treatment of chronic diabetic foot wounds, demonstrating promising clinical translation and application prospects.
[0009] To achieve the above objectives, the present invention provides the following technical solution:
[0010] This invention discloses a method for preparing a hyperpermeable composite dressing containing heterojunction nanozymes, comprising the following steps:
[0011] S.1 Choline chloride and ethylene glycol were mixed and stirred until homogeneous; then MnCl2·4H2O and poloxamer were added to the system and stirring was continued until homogeneous; then hexamethylenetetramine was added and stirring was continued until homogeneous; then the above reactants were subjected to a solvothermal reaction. After the reaction was completed, the precipitate was centrifuged, washed and collected, and vacuum dried to obtain a solid powder; then calcined to obtain the Mn-based precursor.
[0012] S.2 The Mn-based precursor was dispersed in a mixed solvent of ethanol and deionized water and ultrasonically dispersed. Then Ce(NO3)3·6H2O was added and magnetically stirred. Under stirring conditions, NH4HCO3 aqueous solution was slowly added and a water bath reaction was carried out. Then AA was added and a water bath reaction was carried out again. After the reaction was completed, the precipitate was collected by centrifugation. The obtained precipitate was heat-treated to obtain CeO2 / Mn3O4 nanozyme.
[0013] S.3 CeO2 / Mn3O4 nanozymes were ultrasonically dispersed in anhydrous ethanol to obtain a nanozyme dispersion; then glycine was dissolved in deionized water and vitamin D3 was dissolved in anhydrous ethanol, and the two were mixed and dispersed by shaking; under stirring conditions, the functional component mixture was slowly added dropwise to the nanozyme dispersion, and then stirred in the dark. After the reaction was completed, the precipitate was collected by centrifugation to obtain the nanozyme loaded with functional components, which was denoted as intermediate product A;
[0014] S.4 Hyaluronic acid was dispersed in deionized water to obtain a hyaluronic acid solution; then, intermediate product A was added to the hyaluronic acid solution under stirring, and non-covalent surface adsorption modification was carried out under light-protected stirring. After the reaction was completed, the precipitate was collected by centrifugation to obtain HA@CeO2 / Mn3O4 nanozyme.
[0015] S.5 Carbomer, medical glucose syrup as a local hypertonic component, and HA@CeO2 / Mn3O4 nanozyme were added to deionized water and magnetically stirred, followed by swelling for 20-28 hours; finally, the pH of the system was adjusted to neutral with NaOH solution to obtain HA@CeO2 / Mn3O4 dressing.
[0016] Preferably, in step S.1, the conditions for the solvothermal reaction are: temperature 90-115℃, time 5-7h; and the calcination conditions are: heating rate 5℃ / min, calcination temperature 280-330℃, calcination time 2-4h.
[0017] Preferably, in step S.1, the molar ratio of choline chloride to MnCl2·4H2O is 120:2-5; the molar ratio of choline chloride to hexamethylenetetramine is 120:4-7; and 180-230 mg of poloxamer and 20-30 mL of ethylene glycol are added for every 120 mmol of choline chloride.
[0018] Preferably, in step S.2, the conditions for the first water bath reaction are: reaction temperature of 65-75℃ and time of 4-6h; the conditions for the second water bath reaction are: reaction temperature of 75-85℃ and time of 0.5-1.5h; and the conditions for heat treatment are: nitrogen atmosphere, heating rate of 2℃ / min, heat treatment temperature of 270-310℃ and time of 2.5-4h.
[0019] Preferably, in step S.2, 300 mg of Mn-based precursor is used as the measurement standard, Ce(NO3)3·6H2O is 0.4-0.6 mmol, NH4HCO3 is 4-7 mmol, ascorbic acid is 0.9-1.2 mmol, and ethanol / deionized water mixed solvent is 55-70 mL.
[0020] Preferably, in step S.3, the mass-to-volume ratio of the CeO2 / Mn3O4 nanozyme to anhydrous ethanol is 300:35-50, mg / mL; the mass-to-volume ratio of the glycine to deionized water is 180-230:25-40, mg / mL; the mass-to-volume ratio of vitamin D3 to anhydrous ethanol is 20-30:15-25, mg / mL; and the mass ratio of the CeO2 / Mn3O4 nanozyme, glycine, and vitamin D3 is 300:180-230:20-30.
[0021] Preferably, in step S.4, the mass-to-volume ratio of hyaluronic acid to deionized water is 600-800:25-40, mg / mL; and the mass ratio of intermediate product A to hyaluronic acid is 300:600-800.
[0022] Preferably, in step S.5, the mass ratio of carbomer, medical glucose syrup, and HA@CeO2 / Mn3O4 nanozyme is 1:35-55:0.45-0.6, and the mass-to-volume ratio of carbomer to deionized water is 1:120-180, g / mL.
[0023] Accordingly, a hyperpermeable composite dressing containing heterojunction nanozymes prepared by the preparation method is provided, wherein the composite dressing comprises carbomer, medical glucose syrup and HA@CeO2 / Mn3O4 nanozymes.
[0024] Accordingly, the application of a hyperpermeable composite dressing containing heterojunction nanozymes prepared by the aforementioned preparation method in the preparation of a drug for treating chronic diabetic foot wounds.
[0025] The present invention has the following beneficial effects:
[0026] (1) This invention combines nanozymes with SOD (superoxide dismutase) and CAT (catalase) activities with a hypertonic dressing system, loads functional components (vitamin D3 and glycine) onto the nanozymes, and then modifies the surface with hyaluronic acid (HA) to construct a hypertonic composite dressing suitable for the treatment of chronic diabetic foot wounds. The prepared nanozymes have a high specific surface area and abundant pore structure, which is beneficial for the loading of vitamin D3 and glycine. At the same time, combined with the surface modification effect of hyaluronic acid, the release stability of vitamin D3 in the complex exudative environment of the wound can be improved, thus providing a basis for local sustained action.
[0027] (2) This invention uses a ChCl (choline chloride) / EG (ethylene glycol) eutectic solvent system to construct the reaction environment, and combines it with F127 as a soft template and structure directing agent, which helps to improve the pore structure characteristics of the material. The eutectic solvent has high viscosity and strong hydrogen bonding and solvation capabilities, which can provide a certain confinement effect during the reaction, thereby facilitating the formation of a material with a high specific surface area (176.3 m²). 2 The reaction environment also facilitates the effective dispersion of Ce species and the formation of defect structures, thereby obtaining CeO2 / Mn3O4 nanozymes with good catalytic activity, providing a material basis for scavenging excess ROS, alleviating oxidative stress and inflammatory responses.
[0028] (3) In this invention, multiple functional components are loaded onto nanozymes, and then further modified with non-covalent HA adsorption on their surface, thereby facilitating the sustained release of the functional components. HA has good hydrophilicity, and after modification, it can form a stable hydration layer in an aqueous environment, increasing the diffusion resistance of the functional components and prolonging the diffusion path, thus changing the release of the functional components from a relatively rapid release to a more gradual and sustained release. At the same time, hyaluronic acid can also form a dynamic balance of adsorption and desorption with the functional components through interactions such as hydrogen bonding, electrostatic interaction, or physical adsorption, further regulating the release rate. Therefore, the composite dressing obtained by this invention helps to reduce the risk of burst release of local drugs and improve the sustained action of functional components in the complex microenvironment of chronic diabetic foot wounds.
[0029] (4) The HA@CeO2 / Mn3O4 dressing prepared in this invention combines the exudate management function of a hypertonic dressing with the ROS (reactive oxygen species) scavenging function of nanozymes. The hypertonic system helps absorb wound exudate, reduces local water activity, and assists in inhibiting microbial proliferation. The CeO2 / Mn3O4 nanozyme can scavenge excess ROS, reduce oxidative stress, and alleviate inflammatory responses. The loaded functional components (vitamin D3 and glycine) and hyaluronic acid modification further contribute to improving the persistence of local effects. Based on the above-mentioned synergistic effects of multiple mechanisms, the dressing prepared in this invention can effectively promote wound healing in the treatment of chronic diabetic foot wounds, with a wound healing rate of up to 98.4%, showing great application potential. Attached Figure Description
[0030] Figure 1 The image shows the X-ray diffraction (XRD) pattern of the product (nanozyme) from step S.2 of Example 1.
[0031] Figure 2 Scanning electron microscope and elemental mapping (SEM EDS-mapping) of the product (nanozyme) in step S.2 of Example 1 ( Figure 2 a is the SEM image; Figure 2 b is the distribution map of Mn elements; Figure 2 c represents the distribution of Ce elements; Figure 2 (d is the distribution map of element O).
[0032] Figure 3 This is a high-resolution transmission electron microscope (HRTEM) image of the product (nanozyme) from step S.2 of Example 1.
[0033] Figure 4 Electron paramagnetic resonance (EPR) test images of the products (nanozymes) in step S.2 of Example 1, Comparative Example 1, and Comparative Example 2;
[0034] Figure 5 X-ray photoelectron spectroscopy (XPS) spectra of the products (nanozymes) from step S.2 of Examples 1, Comparative Examples 1 and 2.
[0035] Figure 6 The UV-Vis absorption spectra of the POD activity of the products (nanozymes) in step S.2 of Examples 1-3 and Comparative Examples 1-3 are shown.
[0036] Figure 7 The graphs show the SOD activity evaluation test results of the products (nanozymes) in step S.2 of Examples 1-3 and Comparative Examples 1-3;
[0037] Figure 8The CAT activity evaluation test results are shown for the products (nanozymes) of step S.2 in Examples 1-3 and Comparative Examples 1-3.
[0038] Figure 9 The cumulative drug release rate curves for samples from Example 1 and Comparative Examples 5-6 are shown.
[0039] Figure 10 Images showing the healing of chronic diabetic foot wounds in rat models of Example 1 and Comparative Examples 1-6; wherein, Figure 10 Image a shows the healing process of a chronic diabetic foot ulcer in a rat model of the sample from Example 1. Figure 10 b shows images of chronic wound healing in diabetic foot ulcers of rat models from Comparative Examples 1-6. Detailed Implementation
[0040] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0041] Unless otherwise specified, the technical means used in the implementation examples are conventional means well known to those skilled in the art.
[0042] This invention provides a method for preparing a hypertonic composite dressing containing heterojunction nanozymes, and more particularly, a method for preparing a hypertonic dressing containing HA-modified CeO2 / Mn3O4 nanozymes loaded with functional components (vitamin D3 and glycine), comprising the following steps:
[0043] S.1: Choline chloride (ChCl) and ethylene glycol (EG) were mixed and stirred until homogeneous; then MnCl2·4H2O and poloxamer were added to the system and stirred until homogeneous; then hexamethylenetetramine (HMTA) was added and stirred until homogeneous; then the above reactants were subjected to a solvothermal reaction, and after the reaction was completed, the mixture was washed three times by centrifugation with deionized water and anhydrous ethanol and the precipitate was collected. After vacuum drying at 60°C for 8 h, a solid powder was obtained; then calcined in a muffle furnace to obtain the Mn-based precursor.
[0044] The molar ratio of ChCl to MnCl2·4H2O is 120:2-5; the molar ratio of ChCl to HMTA is 120:4-7; and 180-230 mg of poloxamer and 20-30 mL of ethylene glycol are added for every 120 mmol of choline chloride.
[0045] The stirring conditions are: temperature 50-65℃, time 10-20 min. The solvothermal reaction conditions are: temperature 90-115℃, time 5-7 h. The calcination conditions are: heating rate 5℃ / min, calcination temperature 280-330℃, calcination time 2-4 h.
[0046] S.2: The Mn-based precursor was dispersed in a mixed solvent of ethanol and deionized water and ultrasonically dispersed for 15-25 min. Cerium nitrate (Ce(NO3)3·6H2O) was then added and magnetically stirred for 1.5-2.5 h. Ammonium bicarbonate (NH4HCO3) aqueous solution was slowly added under stirring and a water bath reaction was carried out at 65-75℃ for 4-6 h. Ascorbic acid (AA) was then added and a water bath reaction was carried out again at 75-85℃ for 0.5-1.5 h. After the reaction was completed, the precipitate was collected by centrifugation. The obtained precipitate was placed in a tube furnace for heat treatment to obtain CeO2 / Mn3O4 nanozyme.
[0047] The dosage was based on 300 mg of Mn-based precursor, Ce(NO3)3·6H2O was 0.4-0.6 mmol, NH4HCO3 was 4-7 mmol, AA was 0.9-1.2 mmol, and ethanol / deionized water mixed solvent was 55-70 mL.
[0048] Furthermore, the volume ratio of each component in the ethanol and deionized water mixed solvent is 1:1. The heat treatment conditions are: nitrogen atmosphere, heating rate 2℃ / min, heat treatment temperature 270-310℃, and time 2.5-4h.
[0049] S.3: CeO2 / Mn3O4 nanozymes were ultrasonically dispersed in anhydrous ethanol to obtain a nanozyme dispersion for 10 min. Glycine was then dissolved in deionized water and vitamin D3 was dissolved in anhydrous ethanol. The two were then mixed and dispersed by shaking. The functional component mixture was slowly added dropwise to the nanozyme dispersion under stirring conditions. The mixture was then stirred in the dark. After the reaction was completed, the precipitate was collected by centrifugation to obtain the nanozyme loaded with functional components, which was denoted as intermediate product A.
[0050] The stirring conditions are: 200 rpm, dark environment, and 0.5-1.5 h.
[0051] Furthermore, the mass-to-volume ratio of CeO2 / Mn3O4 nanozyme to anhydrous ethanol is 300:35-50, mg / mL. The mass-to-volume ratio of glycine to deionized water is 180-230:25-40, mg / mL. The mass-to-volume ratio of vitamin D3 to anhydrous ethanol is 20-30:15-25, mg / mL. The mass ratio of CeO2 / Mn3O4 nanozyme, glycine, and vitamin D3 is 300:180-230:20-30.
[0052] It should be noted that the purpose of this step is not to require vitamin D3 to remain completely dissolved at the molecular level throughout the loading process. Rather, vitamin D3 is first dissolved in ethanol, and then, during subsequent mixing and stirring, vitamin D3 and glycine are brought into full contact with the CeO2 / Mn3O4 nanozyme, which has a high specific surface area and abundant pore structure. Loading of the functional components is achieved through pore adsorption and surface adsorption. Therefore, the addition of deionized water may slightly alter the apparent solubility of vitamin D3, but it does not affect the successful loading of vitamin D3 onto the nanozyme carrier in this step.
[0053] S.4: Hyaluronic acid (HA) was dispersed in deionized water and magnetically stirred at 35-45℃ for 15-25 min to obtain a hyaluronic acid solution. Then, intermediate product A was added to the hyaluronic acid solution while stirring, and the mixture was stirred in the dark for 3.5-4.5 h. This allowed hyaluronic acid to form an adsorption-modified layer on the surface of intermediate product A through non-covalent interactions such as hydrogen bonding, electrostatic interactions, and interfacial adsorption. After the reaction, the precipitate was collected by centrifugation to obtain HA@CeO2 / Mn3O4 nanozyme. The mass-to-volume ratio of hyaluronic acid to deionized water was 600-800:25-40 (mg / mL), and the mass ratio of intermediate product A to hyaluronic acid was 300:600-800.
[0054] It should be noted that the purpose of this step is not to chemically crosslink hyaluronic acid with CeO2 / Mn3O4 nanozymes, nor is it to prepare a covalently crosslinked hydrogel with hyaluronic acid as the main component. Therefore, this step does not require the addition of a chemical crosslinking agent. In this invention, HA@CeO2 / Mn3O4 represents the surface adsorption modification of the nanozyme loaded with functional components by hyaluronic acid.
[0055] Hyaluronic acid molecules contain abundant carboxyl and hydroxyl groups, which can form multi-point hydrogen bonds, electrostatic interactions, and interfacial adsorption between hydroxyl groups, metal sites, and loaded functional components on the surface of CeO2 / Mn3O4 nanozymes, thereby forming an adsorption layer of hyaluronic acid on the surface of nanozymes.
[0056] After the reaction in step S.4 is completed, the precipitate is collected by centrifugation, which also helps to remove unadsorbed free hyaluronic acid and obtain HA-modified nanozymes.
[0057] The combination of hyaluronic acid (HA) and nanozymes is a surface modification primarily based on non-covalent interfacial interactions. Therefore, upon re-entry into an aqueous environment, a certain degree of adsorption-desorption dynamic equilibrium may exist, rather than requiring a completely irreversible covalent bond between HA and nanozymes. However, this invention subsequently incorporates HA-modified nanozymes into a carbomer-based composite dressing system, where the gel network further restricts the migration of particles and polymeric components.
[0058] S.5: Carbomer, medical glucose syrup (solid content about 70%) as a local hypertonic component, and HA@CeO2 / Mn3O4 nanozyme were added to deionized water and magnetically stirred, followed by swelling for 20-28 hours; finally, the pH of the system was adjusted to neutral with NaOH solution to obtain HA@CeO2 / Mn3O4 dressing.
[0059] The magnetic stirring conditions were: 200 rpm for 25-40 min. The NaOH solution concentration was 1 mol / L, and the system pH was 6.5-7.5.
[0060] Furthermore, the mass ratio of carbomer, medical glucose syrup, and HA@CeO2 / Mn3O4 nanozyme is 1:35-55:0.45-0.6, and the mass-to-volume ratio of carbomer to deionized water is 1:120-180, g / mL.
[0061] It should be noted that the medical glucose syrup in this invention is not used as a therapeutic active ingredient to supplement glucose or enhance local glucose metabolism, but rather as a hypertonic component in a composite dressing. It maintains a high local solute concentration in the carbomer gel system, thereby creating a certain osmotic pressure gradient, which facilitates the migration of wound exudate towards the dressing side and helps improve the hyperexudative wound environment by reducing local water activity. Therefore, this invention utilizes the physical hypertonic properties of the concentrated syrup in the local dressing system, rather than the systemic metabolic effects produced after glucose enters the body. Furthermore, monitoring of blood glucose levels during treatment revealed no significant increase in blood glucose levels in the rats of Example 1 group, further illustrating that the main effect of the medical glucose syrup in this invention originates from the local hypertonic physical effect, rather than from a systemic blood glucose regulation effect produced after glucose absorption.
[0062] Meanwhile, the dressing described in this invention is applied topically, and its route of administration differs significantly from oral or intravenous glucose administration. Medical glucose syrup is dispersed and fixed within a carbomer-based gel system. The dressing primarily acts on the local wound surface and is changed at regular intervals.
[0063] Furthermore, this invention has validated the composite dressing in a diabetic wound model. In the experiment, a diabetic rat model was first established with blood glucose levels consistently above 16.5 mmol / L for two weeks. Subsequently, a full-thickness skin wound infected with Staphylococcus aureus was constructed, and the composite dressing of this application was applied topically. The results showed that the wound healing rate in the Example 1 treatment group reached 98.4% on day 13, significantly higher than the control groups, indicating that under the formulation, dosage, and local administration conditions used in this application, the composite dressing containing medical glucose syrup did not exhibit an overall effect that hindered the repair of diabetic wounds.
[0064] The technical effects supported by this invention are mainly limited to the local hypertonic effect produced by medical glucose syrup in this composite dressing system and the wound repair effect exhibited by the final composite dressing in a diabetic wound model. Another objective of this invention is to provide an application of the hypertonic composite dressing containing heterogeneous nanozymes prepared by the above method in the preparation of a drug for treating chronic diabetic foot wounds.
[0065] The present invention will be further described below with reference to specific embodiments.
[0066] Example 1
[0067] A method for preparing a hyperpermeable composite dressing containing heterojunction nanozymes includes the following steps:
[0068] S.1: 120 mmol of choline chloride (ChCl) was mixed with 25 mL of ethylene glycol (EG) and magnetically stirred at 60 °C for 25 min until a homogeneous and transparent system was formed, yielding a deep eutectic solvent (DES). Subsequently, 3 mmol of MnCl₂·4H₂O and 200 mg of Pluronic F127 were added to the DES, and stirring was continued at 60 °C for 15 min to ensure complete dissolution and mixing. Then, 5 mmol of hexamethylenetetramine (HMTA) was added, and stirring continued until the system was homogeneous. The above reaction mixture was transferred to a sealed reaction vessel and reacted at 100 °C for 6 h. After the reaction was complete, the product was washed three times each with deionized water and anhydrous ethanol by centrifugation. The precipitate was collected and dried under vacuum at 60 °C for 8 h. Finally, the dried solid was placed in a muffle furnace and heated to 300 °C at a heating rate of 5 °C / min and held at that temperature for 3 h to obtain the Mn-based precursor.
[0069] S.2: 300 mg of Mn-based precursor was added to 60 mL of a 1:1 mixture of ethanol and deionized water and ultrasonically dispersed for 20 min to obtain a homogeneous suspension. Then, 0.5 mmol of cerium nitrate (Ce(NO3)3·6H2O) was added, and the mixture was reacted for 2 h under magnetic stirring. Separately, 6 mmol of ammonium bicarbonate (NH4HCO3) was dispersed in the above reaction system and reacted at 70 °C for 5 h. Subsequently, 1 mmol of ascorbic acid (AA) was added, and the reaction was continued at 80 °C in a water bath for 1 h. After the reaction was complete, the precipitate was collected by centrifugation with deionized water. The precipitate was transferred to a tube furnace and heated to 300 °C at a heating rate of 2 °C / min under a nitrogen atmosphere and held for 3 h. After cooling to room temperature, CeO2 / Mn3O4 nanozyme was obtained.
[0070] S.3: 300 mg of CeO2 / Mn3O4 nanozyme was added to 40 mL of anhydrous ethanol and ultrasonically dispersed for 10 min to obtain a homogeneous nanozyme dispersion. Subsequently, 200 mg of glycine was dissolved in 30 mL of deionized water, and 25 mg of vitamin D3 was dissolved in 20 mL of anhydrous ethanol. The two solutions were then mixed and dispersed by shaking to obtain a functional component mixture. The nanozyme dispersion was placed under magnetic stirring at 200 rpm, and the functional component mixture was slowly added dropwise to the nanozyme dispersion while continuously stirring. After the addition was complete, stirring was continued for 1 h under light-protected conditions. After the reaction was completed, the mixture was centrifuged, and the precipitate was collected to obtain the nanozyme loaded with functional components, denoted as intermediate product A.
[0071] S.4: 700 mg of hyaluronic acid was added to 30 mL of deionized water and magnetically stirred at 40 °C for 20 min to form a homogeneous dispersion. Subsequently, 300 mg of intermediate product A was added to the hyaluronic acid dispersion under continuous stirring, and the reaction was continued for 4 h under light-protected conditions. After the reaction was completed, centrifugation was performed to remove free hyaluronic acid and the precipitate was collected to obtain hyaluronic acid-modified nanozyme, denoted as HA@CeO2 / Mn3O4 nanozyme.
[0072] S.5: 1g carbomer, 50g medical glucose syrup (solid content about 70%) and 500mg HA@CeO2 / Mn3O4 were dispersed in 150mL deionized water and magnetically stirred at 200rpm for 30min, followed by swelling for 24h. Then the pH of the system was adjusted to 7.0 with 1mol / L NaOH solution to obtain HA@CeO2 / Mn3O4 dressing, which was recorded as the sample of Example 1.
[0073] Example 2
[0074] A method for preparing a hyperpermeable composite dressing containing heterojunction nanozymes includes the following steps:
[0075] S.1: 120 mmol of choline chloride (ChCl) was mixed with 20 mL of ethylene glycol (EG) and magnetically stirred at 50 °C for 20 min until a homogeneous and transparent system was formed, yielding a deep eutectic solvent (DES). Subsequently, 2 mmol of MnCl₂·4H₂O and 180 mg of Pluronic F127 were added to the DES, and stirring was continued at 50 °C for 20 min to ensure complete dissolution and mixing. Then, 4 mmol of hexamethylenetetramine (HMTA) was added, and stirring continued until the system was homogeneous. The above reaction mixture was transferred to a sealed reaction vessel and reacted at 90 °C for 7 h. After the reaction, the product was washed three times each with deionized water and anhydrous ethanol by centrifugation. The precipitate was collected and dried under vacuum at 60 °C for 8 h. Finally, the dried solid was placed in a muffle furnace and heated to 280 °C at a heating rate of 5 °C / min and held at that temperature for 4 h to obtain the Mn-based precursor.
[0076] S.2: 300 mg of Mn-based precursor was added to 55 mL of a 1:1 mixture of ethanol and deionized water and ultrasonically dispersed for 15 min to obtain a homogeneous suspension. Then, 0.4 mmol of cerium nitrate (Ce(NO3)3·6H2O) was added, and the mixture was reacted for 1.5 h under magnetic stirring. Separately, 4 mmol of ammonium bicarbonate (NH4HCO3) was dispersed in the above reaction system and reacted at 65 °C for 4 h. Subsequently, 0.9 mmol of ascorbic acid (AA) was added, and the reaction was continued at 75 °C in a water bath for 1.5 h. After the reaction was completed, the precipitate was collected by centrifugation with deionized water. The precipitate was transferred to a tube furnace and heated to 270 °C at a heating rate of 2 °C / min under a nitrogen atmosphere and held for 4 h. After cooling to room temperature, CeO2 / Mn3O4 nanozyme was obtained.
[0077] S.3: 300 mg of CeO2 / Mn3O4 nanozyme was added to 35 mL of anhydrous ethanol and ultrasonically dispersed for 10 min to obtain a homogeneous nanozyme dispersion. Subsequently, 180 mg of glycine was dissolved in 25 mL of deionized water, and 20 mg of vitamin D3 was dissolved in 15 mL of anhydrous ethanol. The two solutions were mixed and dispersed by shaking to obtain a functional component mixture. The nanozyme dispersion was placed under magnetic stirring at 200 rpm, and the functional component mixture was slowly added dropwise to the nanozyme dispersion under continuous stirring. After the addition was complete, stirring was continued for 0.5 h under light-protected conditions. After the reaction was completed, the mixture was centrifuged, and the precipitate was collected to obtain the nanozyme loaded with functional components, denoted as intermediate product A.
[0078] S.4: 600 mg of hyaluronic acid was added to 25 mL of deionized water and magnetically stirred at 35 °C for 25 min to form a homogeneous dispersion. Subsequently, 300 mg of intermediate product A was added to the hyaluronic acid dispersion under continuous stirring, and the reaction was continued for 3.5 h under light-protected conditions. After the reaction was completed, centrifugation was performed to remove unadsorbed free hyaluronic acid and the precipitate was collected to obtain HA-modified nanozyme, denoted as HA@CeO2 / Mn3O4 nanozyme.
[0079] S.5: 1g carbomer, 35g medical glucose syrup (solid content approximately 70%), and 450mg HA@CeO2 / Mn3O4 were dispersed in 120mL deionized water and magnetically stirred at 200rpm for 25min, followed by swelling for 20h. Finally, the pH of the system was adjusted to 6.5 using 1mol / L NaOH solution to obtain the HA@CeO2 / Mn3O4 dressing, designated as Sample 2 of Example.
[0080] Example 3
[0081] A method for preparing a hyperpermeable composite dressing containing heterojunction nanozymes includes the following steps:
[0082] S.1: 120 mmol of choline chloride (ChCl) was mixed with 30 mL of ethylene glycol (EG) and magnetically stirred at 65 °C for 10 min until a homogeneous and transparent system was formed, yielding a deep eutectic solvent (DES). Subsequently, 5 mmol of MnCl₂·4H₂O and 230 mg of Pluronic F127 were added to the DES, and stirring was continued at 65 °C for 10 min to ensure complete dissolution and mixing. Then, 7 mmol of hexamethylenetetramine (HMTA) was added, and stirring continued until the system was homogeneous. The above reaction mixture was transferred to a sealed reaction vessel and reacted at 115 °C for 5 h. After the reaction, the product was washed three times each with deionized water and anhydrous ethanol by centrifugation. The precipitate was collected and dried under vacuum at 60 °C for 8 h. Finally, the dried solid was placed in a muffle furnace and heated to 330 °C at a heating rate of 5 °C / min and held at that temperature for 2 h to obtain the Mn-based precursor.
[0083] S.2: 300 mg of Mn-based precursor was added to 70 mL of a 1:1 mixture of ethanol and deionized water and ultrasonically dispersed for 25 min to obtain a homogeneous suspension. Then, 0.6 mmol of cerium nitrate (Ce(NO3)3·6H2O) was added, and the mixture was reacted under magnetic stirring for 2.5 h. Separately, 7 mmol of ammonium bicarbonate (NH4HCO3) was dispersed in the above reaction system and reacted at 75 °C for 4 h. Subsequently, 1.2 mmol of ascorbic acid (AA) was added, and the reaction was continued at 85 °C in a water bath for 0.5 h. After the reaction was completed, the precipitate was collected by centrifugation with deionized water. The precipitate was transferred to a tube furnace and heated to 310 °C at a heating rate of 2 °C / min under a nitrogen atmosphere and held for 2.5 h. After cooling to room temperature, CeO2 / Mn3O4 nanozyme was obtained.
[0084] S.3: 300 mg of CeO2 / Mn3O4 nanozyme was added to 50 mL of anhydrous ethanol and ultrasonically dispersed for 10 min to obtain a homogeneous nanozyme dispersion. Subsequently, 230 mg of glycine was dissolved in 40 mL of deionized water, and 30 mg of vitamin D3 was dissolved in 25 mL of anhydrous ethanol. The two solutions were then dispersed by shaking to obtain a functional component mixture. The nanozyme dispersion was placed under magnetic stirring at 200 rpm, and the functional component mixture was slowly added dropwise to the nanozyme dispersion while continuously stirring. After the addition was complete, stirring was continued for 1.5 h under light-protected conditions. After the reaction was completed, the mixture was centrifuged, and the precipitate was collected to obtain the nanozyme loaded with functional components, denoted as intermediate product A.
[0085] S.4: 800 mg of hyaluronic acid was added to 40 mL of deionized water and magnetically stirred at 45 °C for 15 min to form a homogeneous dispersion. Subsequently, 300 mg of intermediate product A was added to the hyaluronic acid dispersion under continuous stirring, and the reaction was continued for 4.5 h under light-protected conditions. After the reaction was completed, centrifugation was performed to remove free hyaluronic acid and the precipitate was collected to obtain the hyaluronic acid-modified nanozyme, denoted as HA@CeO2 / Mn3O4 nanozyme.
[0086] S.5: 1g carbomer, 55g medical glucose syrup (solid content approximately 70%), and 600mg HA@CeO2 / Mn3O4 nanozyme were added to 180mL of deionized water. The mixture was magnetically stirred at 200rpm for 40min and then swollen for 28h. Subsequently, the pH of the system was adjusted to 7.5 with 1mol / L NaOH solution to obtain the HA@CeO2 / Mn3O4 dressing, which was designated as Sample 3 of Example.
[0087] Comparative Example 1
[0088] The difference between Comparative Example 1 and Example 1 is that F127 was not added in step S.1, while the other steps remained unchanged, and the resulting product was recorded as Comparative Example 1 sample.
[0089] Comparative Example 2
[0090] The difference between Comparative Example 2 and Example 1 is that in step S.1, the ChCl / EG eutectic solvent was replaced with an equal volume of a mixed solvent of ethanol and water (volume ratio 1:1), while the other steps remained unchanged. The resulting product was recorded as Comparative Example 2 sample.
[0091] Comparative Example 3
[0092] The difference between Comparative Example 3 and Example 1 is that no cerium nitrate was added in step S.2, while the other steps remained unchanged, and the resulting product was recorded as Comparative Example 3 sample.
[0093] Comparative Example 4
[0094] The difference between Comparative Example 4 and Example 1 is that no nanozyme was added. The specific synthesis method was modified as follows: steps S.1 and S.2 were deleted, and in steps S.3, S.4 and S.5, the nanozyme was replaced with an equal mass of polylactic acid. Other steps remained unchanged, and the resulting product was recorded as Comparative Example 4 sample.
[0095] Comparative Example 5
[0096] The difference between Comparative Example 5 and Example 1 is that the nanozyme and other components are simply physically mixed. Specifically, the synthesis method is as follows:
[0097] (1) Disperse 300mg of nanozyme in 40mL of deionized water using ultrasonication; dissolve 1g of carbomer, 25mg of vitamin D3, 200mg of glycine, 700mg of hyaluronic acid and 50g of medical glucose syrup in a mixed solvent of 150mL of deionized water and anhydrous ethanol (volume ratio 8:2), and then disperse and mix them thoroughly.
[0098] (2) The mixture was magnetically stirred at 200 rpm for 30 min and then swollen for 24 h. Finally, the pH of the system was adjusted to 7.0 using 1 mol / L NaOH solution to obtain the comparative sample 5.
[0099] Comparative Example 6
[0100] The difference between Comparative Example 6 and Example 1 is that there is no hyaluronic acid modification, and the other steps remain unchanged. The resulting product is referred to as Comparative Example 6 sample.
[0101] Structural and performance characterization of nanoenzyme materials in examples and comparative studies:
[0102] X-ray diffraction (XRD) was performed on the product (nanozyme) obtained in step S.2 of Example 1 (the test results are shown in [see figure]). Figure 1 (See Table 1) Scanning electron microscopy and elemental mapping (SEM EDS-mapping) tests (test results are shown in Table 1). Figure 2 High-resolution transmission electron microscopy (HRTEM) tests (test results are shown in...) Figure 3 Electron paramagnetic resonance (EPR) test (test results are available in [link to test results]). Figure 4 X-ray photoelectron spectroscopy (XPS) test (test results are shown in...) Figure 5 The adsorption-desorption curves of nitrogen were tested (the test results are shown in Table 1).
[0103] The products (nanozymes) obtained in step S.2 under the synthesis conditions of Examples 2, 3, Comparative Examples 1, 2 and 3 were subjected to XRD phase analysis (test results are shown in Table 1) and nitrogen adsorption-desorption test (test results are shown in Table 1).
[0104] The products (nanozymes) obtained in step S.2 under the synthesis conditions of Comparative Examples 1 and 2 were subjected to EPR testing (the test results are shown in [link to test results]). Figure 4 ) and XPS test (test results can be found in) Figure 5 ).
[0105] The testing method is as follows:
[0106] XRD testing method: Take 10mg of sample and place it on a glass slide. Use an X-ray diffractometer (Rigaku SmartLab SE, Japan) for testing. The test range is 5-70°, the scan rate is 5° / min, the light source is Cu-Kα rays, the tube voltage is 40kV, and the current is 40mA.
[0107] SEM EDS-mapping test method: 5mg of sample was uniformly dispersed on the surface of conductive adhesive and sputtered with gold for 45s using an Oxford Quorum SC7620 sputtering coating instrument at 10mA. Subsequently, the morphology of the sample was photographed using a Zeiss Sigma 300 scanning electron microscope, and elemental mapping analysis was performed using an Oxford Xplore 300 energy dispersive spectrometer. The accelerating voltage for morphology photography was 3kV, and the accelerating voltage for energy dispersive spectroscopy mapping photography was 15kV. The detector was an SE2 secondary electron detector.
[0108] HRTEM test method: Add approximately 1 mg of sample to 5 mL of anhydrous ethanol and sonicate for 30 min to form a uniform dispersion. Then, add a few drops of the dispersion dropwise onto a copper grid. After drying, photograph the morphology (high resolution) using a FEI TalosF200X G2 (USA) with an accelerating voltage of 200 kV.
[0109] EPR testing method: 10 mg of sample was placed in a quartz sample tube, and oxygen vacancy-related defects were tested using an electron paramagnetic resonance spectrometer (Bruker EMXplus-6 / 1, Germany). The test was conducted at room temperature in the X-band, with a microwave frequency of approximately 9.4 GHz, a central magnetic field of approximately 350 mT, a scan width of 100–200 mT, a microwave power of 1 mW, a modulation frequency of 100 kHz, and a modulation amplitude of 0.1 mT. EPR spectra were acquired after resonant cavity tuning and coupling matching.
[0110] XPS test method: After compressing 5 mg of sample into a tablet, attach it to the sample tray and place the sample into the sample chamber of the Thermo Scientific K-Alpha XPS instrument. The pressure in the sample chamber should be less than 2.0 × 10⁻⁶. -7 At mbar, the sample is sent into the analysis chamber with a spot size of 400 μm, an operating voltage of 12 kV, and a filament current of 6 mA; the narrow spectrum scanning pass energy is 50 eV, and the step size is 0.1 eV.
[0111] Nitrogen adsorption-desorption test method: Using the standard degassing station of the Micromeritics instrument, about 50 mg of sample was placed in a sample tube and pretreated for 12 h under vacuum at 120℃. Then, nitrogen adsorption-desorption test was performed on the sample using a Micromeritics ASAP 2460 4-station fully automated specific surface area analyzer under liquid nitrogen at 77k. After the instrument analysis was completed, the isothermal adsorption-desorption curve was obtained. The total specific surface area of the material was obtained by the BET method, the total pore volume of the material was calculated by the liquid nitrogen volume conversion method, and the mesopore ratio and micropore ratio were obtained by the NLDFT method.
[0112] First, we will analyze Example 1 separately. (From...) Figure 1 As can be seen, X-ray diffraction (XRD) tests of the product (nanozyme) in step S.2 of Example 1 showed the simultaneous presence of characteristic diffraction peaks of CeO2 and Mn3O4. The peak positions highly matched those of the CeO2 standard card (PDF#99-000-0623) and the Mn3O4 standard card (PDF#00-024-0734), respectively, indicating that both CeO2 and Mn3O4 crystalline phases were successfully formed in the S.2 product. Figure 2 It can be seen that the product (nanozyme) in step S.2 of Example 1 is in the form of nanoparticles, and the Mn, Ce, and O elements are uniformly distributed. From Figure 3 In the HRTEM image of the product (nanozyme) in step S.2 of Example 1, two sets of clear lattice fringes can be observed, corresponding to CeO2 and Mn3O4 crystal phases respectively, and the two are in close contact at the nanoscale, indicating that a clear heterojunction structure is formed in the S.2 product. Figure 4 The electron paramagnetic resonance (EPR) test results for the S.2 product are provided by... Figure 4 It can be seen that a strong characteristic signal peak exists at g=2.003, indicating a high concentration of oxygen vacancy defects in the material. From... Figure 5 It can be seen that the Ce3d spectrum of the S.2 product shows Ce 3+ The proportion was 25.2%, compared to the comparative proportion Ce 3+ The proportion increased significantly. As shown in Table 1, the S.2 product has a large BET specific surface area, reaching 176.3 m². 2 The total pore volume was 0.46 mL / g. NLDFT analysis revealed that the micropore and mesopore proportions were 35.75% and 53.21%, respectively. This indicates that the S.2 product possesses a hierarchical pore structure composed of micropores, mesopores, and macropores. This hierarchical structure is not determined by a single factor, but rather by the synergistic effect of multiple factors, including the controllable formation of the precursor under deep eutectic solvent reaction conditions, the guiding effect of the F127 template, nanoparticle stacking, and the removal of organic components during subsequent washing and heat treatment. This hierarchical pore structure is beneficial for increasing the specific surface area of the material, promoting reactant mass transfer, and increasing the loading sites for subsequent functional components, thus providing a good structural basis for the catalytic activity of the material and the construction of composite dressings.
[0113] Furthermore, the S.2 product is rich in oxygen vacancies, possibly because the CeO2 and Mn3O4 phases are in close contact at the nanoscale and form a heterojunction. Lattice mismatch and changes in the local coordination environment at the interface easily induce the formation of defect sites. In addition, the participation of ascorbic acid and the heat treatment under nitrogen protection during the preparation process create a relatively reducing atmosphere, which is conducive to the removal and migration of some lattice oxygen, thereby promoting the formation and retention of oxygen vacancies.
[0114] Examples 2 and 3 were analyzed. Table 1 shows that the products (nanozymes) obtained in step S.2 of both Examples 2 and 3 exhibited the presence of two metal oxide phases, CeO2 and Mn3O4, indicating that a CeO2 / Mn3O4 composite structure could be formed under different preparation conditions. Furthermore, both samples maintained a large specific surface area and a hierarchical porous structure. The BET specific surface area of the sample in Example 2 was 175.5 m². 2 The total pore volume was 0.45 mL / g, and NLDFT analysis showed that the proportions of micropores and mesopores were 36.93% and 52.34%, respectively; the BET specific surface area of the sample in Example 3 was 170.9 m² / g. 2 / g, with a total pore volume of 0.46mL / g, and micropores and mesopores accounting for 33.52% and 51.07%, respectively.
[0115] Analysis was performed on Comparative Examples 1, 2, and 3. Table 1 shows that the products (nanozymes) obtained in step S.2 of Comparative Examples 1 and 2 both consist of two crystalline phases: CeO2 and Mn3O4, indicating that a CeO2 / Mn3O4 composite structure can still be formed under the corresponding conditions. However, the product (nanozyme) obtained in step S.2 of Comparative Example 3 only showed the Mn3O4 crystalline phase, and no CeO2-related diffraction peaks were detected, indicating that the CeO2 phase cannot be formed without the introduction of a Ce source. Furthermore, Table 1 shows that the products (nanozymes) obtained in step S.2 of Comparative Examples 1-3 all exhibited varying degrees of change in specific surface area, pore volume, and pore size distribution. The BET specific surface area of the sample in Comparative Example 1 was 65.9 m². 2 The total pore volume was 0.22 mL / g, and NLDFT analysis showed that the mesoporous proportion was 27.41% and the microporous proportion was 49.96%; the BET specific surface area of the comparative example 2 sample was 78.4 m² / g. 2 The total pore volume was 0.31 mL / g, the mesoporous proportion was 32.95%, and the microporous proportion was 40.08%. Compared with the sample of the example, the specific surface area and total pore volume of Comparative Example 1 and Comparative Example 2 were significantly reduced, and the mesoporous proportion was also reduced, indicating that the corresponding preparation conditions were not conducive to the formation of hierarchical pore structure. The BET specific surface area of the sample of Comparative Example 3 was 159.8 m² / g. 2 The total pore volume was 0.41 mL / g, and NLDFT analysis showed that the mesoporous proportion was 35.66% and the microporous proportion was 47.53%. Although Comparative Example 3 still maintained a high specific surface area and pore volume, its pore size distribution differed from that of the example sample, indicating that its pore structure was affected to some extent.
[0116] Depend on Figure 4 It can be seen that oxygen vacancy-related signal peaks were observed in the products (nanozymes) obtained in step S.2 of both Comparative Example 1 and Comparative Example 2, but their peak intensities were significantly weakened compared to Example 1, indicating that the oxygen vacancy concentrations in both comparative example samples were reduced. Figure 5 As shown, the Ce3d spectra of the products (nanozymes) obtained in step S.2 of Comparative Example 1 and Comparative Example 2 both show Ce3d... 3+ The existence of Ce, but its Ce 3+ The proportions were 16.1% and 14.4%, respectively, both lower than the Ce content in the product (nanozyme) obtained in step S.2 of Example 1. 3+ The proportion decreased significantly, indicating that the Ce content in the material under the control conditions was lower. 3+ / Ce 4+ The proportions changed.
[0117] For Comparative Example 1 sample, its BET specific surface area, total pore volume, and mesoporous ratio were all significantly reduced, while the oxygen vacancy-related signal intensity was weakened, and Ce... 3+The proportion decreased. This may be because F127 acts as a soft template and structure guide in the reaction system, contributing to the formation of hierarchical pore structures. Without the addition of F127, the material can still form a certain pore structure, but the ability to control the pore structure decreases, potentially leading to the formation of more irregular pores. Furthermore, changes in pore structure may affect the exposure of surface defect sites, weakening oxygen vacancy-related defect signals and affecting Ce... 3+ The results were consistent with the decrease in the proportion. For the Comparative Example 2 sample, its BET specific surface area, total pore volume, and mesoporous proportion all decreased, while the oxygen vacancy concentration and Ce2 content also decreased. 3+ The proportions are lower than in Example 1. This may be because replacing the ChCl / EG eutectic solvent with a mixed solvent of ethanol and water changes the reaction medium from a confined environment with high viscosity, strong hydrogen bonding, and strong solvation ability to a low viscosity and weakly structured environment. This weakens the ability to regulate the nucleation and growth process of the precursor, resulting in a decrease in the control effect of the material's pore structure and affecting the formation state and defect structure of Ce species. The above changes alter the pore structure characteristics and defect-related structures of the obtained samples. Therefore, the mixed solvent of ethanol and water is not conducive to the formation of nanozyme materials with well-developed pore structures and abundant defect sites. For the Comparative Example 3 sample, no CeO2 crystalline phase was formed; it only exhibited a Mn3O4 structure, and its pore structure parameters differed from those of Example 1. This may be because the change in material composition affected the particle formation and stacking mode. The presence of heterogeneous components may affect particle formation and stacking mode, and single oxides are more likely to exhibit particle aggregation characteristics different from composite systems, thus leading to changes in the pore structure.
[0118] POD, SOD and CAT activity tests:
[0119] The products (nanozymes) obtained in step S.2 of Examples 1, 2, 3, Comparative Examples 1, 2, and 3 were subjected to POD activity testing (test results are shown in...). Figure 6 SOD activity test (test results are available in [link to test results]). Figure 7 ) and CAT activity test (test results are shown in Figure 8 The testing method is as follows:
[0120] POD activity test method: Suspension of the test sample (1 mg / mL), TMB (3,3',5,5'-tetramethylbenzidine) (1 mM), and H2O2 (60 mM) solution were prepared using pure water. Subsequently, 30 µL of the suspension from Example 1, 120 µL of H2O2, and 150 µL of TMB were mixed in 2700 µL of sodium acetate-acetic acid (NaAc-HAc, pH=4, 0.2 M) buffer solution and incubated at room temperature for 30 min. The absorbance of the reaction solution was then measured at 652 nm using a UV-Vis spectrophotometer.
[0121] SOD Activity Assay Method: The nanozymes obtained in Step S.2 of Examples 1-3 and Comparative Examples 1-3 were prepared into dispersions with concentrations of 250, 500, 750, and 1000 μg / mL, respectively. 20 µL of the dispersion was added to a 96-well plate, followed by 160 µL of WST-8 / enzyme working solution (containing SOD detection buffer, WST-8, and xanthine oxidase) and 20 µL of xanthine reaction initiation solution. Blank 1 and Blank 2 were set as absorbance correction wells to correct for the influence of background absorption and non-specific color development on the measurement results. After incubating the reaction system at 37°C in the dark for 30 min, the absorbance was measured at 450 nm. The SOD inhibition rate was calculated using the inhibition rate formula, and a concentration-inhibition rate curve was plotted to characterize the SOD-like activity of the material. It should be noted that Blank 1 and Blank 2 were only used as correction wells in the calculation of the SOD (superoxide dismutase) inhibition rate, and their results have been used for... Figure 7 The SOD (superoxide dismutase) inhibition rate shown is not included in the calculation of the independent test sample group that is parallel to the examples and comparative examples. Figure 7 It is presented separately as an independent data series.
[0122] CAT activity assay method: Add 500 µg of the test sample to 5 mL of 50 mM H2O2 solution to make the final concentration of the solution 100 µg / mL. -1 After stabilizing for 5 minutes, the dissolved oxygen concentration was recorded every 60 seconds for 20 minutes.
[0123] Depend on Figure 6 It can be seen that the products (nanozymes) obtained in step S.2 of Examples 1-3 generally exhibited low POD activity. Figure 7 and Figure 8 It can be seen that the samples in Examples 1-3 all exhibited good SOD and CAT enzyme activities, indicating that the obtained CeO2 / Mn3O4 nanozymes mainly exhibited good ROS scavenging performance. Taking the sample in Example 1 as an example, its good SOD and CAT enzyme activities may be related to the high proportion of Ce in the material. 3+ This is related to the abundant oxygen vacancy structure, and the two corroborate each other, which is conducive to promoting Ce 3+ / Ce 4+ Reversible cycle, thereby enhancing the control of O2· - The adsorption, activation, and conversion of H2O2 are also facilitated. Simultaneously, the construction of the CeO2 / Mn3O4 heterostructure may aid in charge transfer and multivalent state cycling processes at the interface. Furthermore, the larger specific surface area and hierarchical pore structure are beneficial for the exposure of active sites and reactant / product mass transfer, thereby promoting the overall catalytic performance of the material.
[0124] Depend on Figure 6It can be seen that the products (nanozymes) obtained in step S.2 of both Comparative Example 1 and Comparative Example 2 exhibited relatively weak POD activity. Figure 7 and Figure 8 It can be seen that both Comparative Example 1 and Comparative Example 2 samples exhibit certain SOD and CAT enzyme activities, but their ROS scavenging ability is significantly weaker than that of Example 1. The reduced performance of Comparative Example 1 sample may be related to the pore structure changes caused by the absence of F127. Due to the absence of F127, the specific surface area, total pore volume, and mesoporous ratio of the material all decreased, affecting the exposure of active sites and the mass transfer conditions of reactants. Meanwhile, Ce... 3+ A decrease in the proportion usually indicates a reduction in active sites on the material surface that can participate in redox cycles, which is detrimental to the adsorption, activation, and conversion of reaction substrates, thereby weakening the overall catalytic performance of the material. For Comparative Example 2, the performance reduction may be due to the weakened pore structure regulation effect after replacing the ChCl / EG eutectic solvent with a mixed solvent of ethanol and water, resulting in a decrease in specific surface area, total pore volume, and mesopore proportion, leading to a decrease in the exposure of active sites and a deterioration in reactant mass transfer conditions. Meanwhile, Ce... 3+ A reduced ratio may also decrease the number of active sites that can participate in the redox cycle, which is not conducive to the adsorption, activation and transformation of the reaction substrate, and ultimately weakens the overall catalytic performance of the material.
[0125] Depend on Figure 6 , Figure 7 and Figure 8 It can be seen that, compared with Example 1, the product (nanozyme) obtained in step S.2 of Comparative Example 3 showed significantly enhanced POD activity, while the activities of SOD and CAT enzymes significantly decreased. These results indicate that the catalytic conversion of H2O2 by single-phase Mn3O4 nanozymes is more inclined towards the POD reaction pathway, while the CeO2 / Mn3O4 heterojunction nanozyme exhibits more pronounced CAT reaction characteristics. This may be because the formation of the heterojunction interface alters the surface electronic structure and active site environment, thereby regulating the adsorption and activation mode of H2O2 on the material surface, making it more conducive to the decomposition of H2O2 into H2O and O2. Single-phase Mn3O4's activation of H2O2 is more biased towards the POD reaction pathway. Furthermore, the decreased SOD activity may be due to the lack of interfacial charge coupling and multi-valence synergistic effects brought about by the heterojunction, which weakens the surface redox cycle capacity, thereby reducing its ability to react with superoxide anions.
[0126] Functional component content determination and release performance evaluation:
[0127] The mass ratio of vitamin D3 to glycine was determined and calculated for the HA-modified drug-loaded nanozymes obtained in step S.4 of Examples 1 and Comparative Examples 1-3, and the results are shown in Table 2.
[0128] The cumulative release rate of vitamin D3 was determined for the final composite dressings prepared in Example 1, Comparative Example 5, and Comparative Example 6. The results are shown in [Figure Number]. Figure 9 .
[0129] The testing method is as follows:
[0130] Vitamin D3 mass ratio determination: 500 mg of the sample was taken and 100 mL of anhydrous ethanol was added. The mixture was sonicated at room temperature for 60 min to fully dissolve and release the vitamin D3 loaded in the sample into the solution. The resulting dispersion was then centrifuged at 10,000 rpm for 10 min, and the supernatant was collected. This process was repeated three times. After filtration through a 0.22 μm organic filter membrane, the sample was analyzed by high-performance liquid chromatography (HPLC). A C18 reversed-phase column was used for separation, with methanol as the mobile phase and a detection wavelength of 280 nm. A standard curve was established based on vitamin D3 standards, and the actual mass ratio of vitamin D3 in the sample was calculated using the following formula: Vitamin D3 mass ratio = (mass of vitamin D3 detected / mass of sample taken) × 100%.
[0131] Glycine mass ratio determination: 500 mg of the sample was added to 50 mL of 6 mol / L hydrochloric acid solution and treated at 110℃ for 24 h. The acidic environment promoted the desorption of glycine from the nanozyme carrier surface and its entry into the solution system. After treatment, the resulting solution was concentrated to remove acid, then diluted to 50 mL with deionized water. After filtration through a 0.22 μm aqueous filter membrane, the solution was analyzed using an amino acid analyzer. A standard curve was established based on glycine standards, and the actual glycine content in the sample was calculated. The glycine mass ratio was calculated using the following formula:
[0132] Glycine mass ratio = (mass of glycine detected / mass of sample taken) × 100%.
[0133] The method for determining the cumulative release rate of vitamin D3 is as follows: Before the release experiment, the initial vitamin D3 content in the sample was determined by HPLC for calculation of the cumulative release rate. 45g of the sample was added to 100mL of PBS buffer (pH=7.4), and the release experiment was conducted under constant temperature and shaking conditions at 37℃. At set time points (0, 3, 6, 9, 12, 15, 18, 21, and 24 h), 1mL of the release solution was collected, centrifuged, filtered, and the vitamin D3 concentration in the release solution was detected by high-performance liquid chromatography. Simultaneously, an equal volume of fresh PBS buffer was added after each sampling to maintain a constant total volume of the release system.
[0134] The cumulative vitamin D3 release rate was calculated based on the vitamin D3 release levels measured at different time points.
[0135] Vitamin D3 cumulative release rate (%) = (cumulative released vitamin D3 mass / total initial vitamin D3 mass in the sample) × 100%.
[0136] The cumulative mass of vitamin D3 released was calculated based on the vitamin D3 concentration in the release solution at each time point, with compensation and correction for vitamin D3 loss due to timed sampling during the experiment. The specific calculation formula is as follows:
[0137] M t =C t V+ΣCiV s
[0138] In the formula, M t C represents the cumulative mass of vitamin D3 released at time point t; t V represents the concentration of vitamin D3 in the released solution at time point t; V represents the total volume of the release system; C represents the concentration of vitamin D3 in the released solution at time point t. i V represents the concentration of vitamin D3 in the released solution during the i-th sampling. s This represents the volume of each sample taken.
[0139] As shown in Table 2, the mass of vitamin D3 and glycine detected in the sample obtained in step S.4 of Example 1 were 19.0 mg and 82.0 mg, respectively, with calculated mass ratios of 3.8 wt% and 16.4%. In contrast, the content of functional components in Comparative Examples 1-3 all decreased, but there were significant differences among the different comparative examples. Among them, the mass of vitamin D3 and glycine detected in the sample obtained in step S.4 of Comparative Example 1 were 9.0 mg and 45.5 mg, respectively, with mass ratios of 1.8 wt% and 9.1%, showing the most significant decrease. The mass of vitamin D3 and glycine detected in the sample obtained in step S.4 of Comparative Example 2 were 11.5 mg and 54.0 mg, respectively, with mass ratios of 2.3 wt% and 10.8%, showing the second most significant decrease. The mass of vitamin D3 and glycine detected in the sample obtained in step S.4 of Comparative Example 3 were 13.5 mg and 64.5 mg, respectively, with mass ratios of 2.7 wt% and 12.9%, showing a relatively smaller decrease in the content of functional components. The above results indicate that changes in material structure characteristics affect the binding capacity of functional components. Specifically, in Comparative Example 1, the absence of F127 significantly reduced the specific surface area, total pore volume, and mesopore ratio, weakening the pore structure regulation effect and consequently reducing the binding capacity of functional components. In Comparative Example 2, replacing the ChCl / EG eutectic solvent with a mixture of ethanol and water affected the material's pore structure regulation, resulting in decreased specific surface area, total pore volume, and mesopore ratio, thus reducing the content of functional components. For Comparative Example 3, although it still possessed a high specific surface area and certain pore structure characteristics, the lack of a CeO2 / Mn3O4 composite structure altered the material's structural characteristics, leading to a lower binding capacity of functional components compared to Example 1.
[0140] Depend on Figure 9 It can be seen that the vitamin D3 loaded in the sample of Example 1 exhibited a relatively slow release rate, with a cumulative release rate of 95% at 24 hours. In contrast, the vitamin D3 release rates in Comparative Examples 5 and 6 were significantly faster. Among them, Comparative Example 5 showed the fastest vitamin D3 release rate, reaching a cumulative release rate of 91% at 9 hours, which was significantly higher than that of Example 1. This may be because Comparative Example 5 only used a physical mixing method and did not load vitamin D3 and glycine into the nanozyme structure. The system changed from a structure-controlled state to a disordered blending state, making the functional components mainly in a free state, which made it difficult to achieve continuous release and thus shortened the local effective exposure time. The cumulative release rate of Comparative Example 6 reached 94% at 15 hours, which was significantly higher than that of Example 1. This may be because although Comparative Example 6 loaded vitamin D3 and glycine into the nanozyme, it did not undergo further HA modification, lacking the surface modification layer, diffusion barrier, and hydration protection provided by HA, which further accelerated the release rate of the functional components.
[0141] Evaluation of the effect of composite dressings on the repair of chronic diabetic foot wounds:
[0142] Wound healing experiments were conducted on samples from Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5, and Comparative Example 6 (test results are shown in...). Figure 10 (and Table 3).
[0143] Wound Healing Experimental Testing Methods: Construction of Diabetic Rats and Back Wound Model: All animal experiments complied with the "Animal Care Guidelines". Male SD rats aged 6-8 weeks and weighing 200-220g were selected as experimental animals. The diabetic wound preparation steps were as follows: After feeding rats a high-fat diet for 2 weeks, they were fasted for 12 hours and then intraperitoneally injected with streptozotocin (STZ) at a dose of 30 mg / kg. STZ was dissolved in freshly prepared citrate buffer (pH 4.5). The rats were fed a high-fat diet after injection. One week later, blood glucose levels were measured by tail vein sampling. Rats with blood glucose levels above 16.5 mmol / L for two consecutive weeks were identified as diabetic rats. Next, a circular surgical wound with a diameter of 1 cm was made on the back of the rat under ether anesthesia using medical scissors. Subsequently, 100 μL of Staphylococcus aureus suspension with a concentration of 1×10^8 CFU / mL was evenly dripped onto the wound surface, covered with sterile gauze, and secured with medical tape. Twenty-four hours after infection, rats were randomly divided into seven groups: Example 1 group and Comparative Examples 1-6 groups. Each group was treated with the corresponding composite dressing prepared in Example 1 and Comparative Examples 1-6, respectively. 200 μL of the corresponding composite dressing was applied evenly to the rat wound surface each time, maintaining a consistent dosage volume across all groups. The dressing was changed every 24 hours. Wound condition was measured on days 0, 3, 7, 10, and 13. The healing rate (%) was calculated as follows: [(A0-A...]...] t The wound healing rate is calculated as [A0] × 100%, where A0 is the initial wound area, A... t This represents the residual wound area at each time point.
[0144] Depend on Figure 10As shown in Table 3, the sample treatment group of Example 1 exhibited better wound repair in the diabetic foot chronic wound model, with a wound healing rate of 98.4% on day 13, significantly higher than that of the comparative sample treatment groups. The superior wound repair effect of the Example 1 sample may be related to the synergistic effect of its multiple components. First, medical glucose syrup, as a locally hypertonic component, can promote the migration of wound exudate to the dressing side by forming a local osmotic pressure gradient, reducing wound edge maceration and local edema, and helping to improve the hyperexudative wound environment. This effect mainly comes from the local hypertonic physical effect, rather than the systemic metabolic effect of glucose after entering the body. Second, CeO2 / Mn3O4 nanozyme has good SOD / CAT enzyme activity, which helps to reduce the local ROS level of the wound and alleviate oxidative stress. In addition, vitamin D3 and glycine functional components help to regulate the local immune environment and promote extracellular matrix-related repair processes. At the same time, hyaluronic acid surface modification can reduce the release rate of functional components by forming a hydration layer and regulating the diffusion process of functional components, thereby helping to maintain local sustained effects. Therefore, the synergistic effect of multiple functional components promotes the repair of chronic diabetic foot wounds.
[0145] Depend on Figure 10 As shown in Table 3, the wound healing rate of the Comparative Example 1 sample treatment group on day 13 was 60.7%, which was significantly lower than that of the Example 1 sample. The reason for this may be that the pore structure characteristics and SOD / CAT enzyme activity of the Comparative Example 1 sample were reduced, resulting in a weakened function of functional components and a reduced ability to clear ROS in the wound, which is not conducive to the relief of oxidative stress and the improvement of the wound microenvironment, ultimately leading to a decrease in wound repair effect.
[0146] On day 13, the wound healing rate of the Comparative Example 2 sample group was 64.4%, which was lower than that of the Sample of Example 1. This was because the pore structure regulation effect of the Comparative Example 2 sample was weakened, and the activities of SOD and CAT enzymes were reduced, affecting their ability to maintain the function of functional components and clear local ROS from the wound. Therefore, the wound repair effect was lower than that of the Sample of Example 1.
[0147] On day 13, the wound healing rate of the Comparative Example 3 sample treatment group was 67.5%, which was lower than that of the Sample of Example 1. Because the Comparative Example 3 sample did not form a CeO2 / Mn3O4 complex structure, its enzyme activity characteristics changed, showing a decrease in SOD and CAT activity and an increase in POD activity, which weakened its ability to regulate oxidative stress in the wound and ultimately affected the wound repair effect.
[0148] On day 13, the wound healing rate of Comparative Example 4 was 48.2%, significantly lower than that of Example 1. This may be because the Comparative Example 4 sample lacked the nanozyme component, thus the system no longer possessed the porous structure and high specific surface area provided by nanozymes, leading to a decrease in the adsorption, storage, and sustained action of functional components. Simultaneously, the lack of SOD / CAT enzyme activity provided by nanozymes reduced its ability to scavenge local ROS in the wound, which is detrimental to oxidative stress relief and wound microenvironment stability.
[0149] On day 13, the wound healing rate of Comparative Example 5 was 51.6%, lower than that of Example 1. Because Comparative Example 5 used a physical mixing method, it failed to achieve effective binding between the functional components and the nanozyme structure, resulting in a lack of structural regulation in the release process of the functional components and a decreased local sustained effect. Furthermore, the material structural characteristics and enzyme activity may be affected under physical mixing conditions, further weakening the regulatory effect on the wound microenvironment.
[0150] On day 13, the wound healing rate of Comparative Example 6 was 55.7%, lower than that of Example 1. Although Comparative Example 6 still contained nanozymes loaded with functional components, the lack of hyaluronic acid modification weakened the regulatory effect of functional component release, which was not conducive to maintaining a sustained and effective local action. Therefore, the overall wound repair effect of Comparative Example 6 was lower than that of Example 1.
[0151] In addition, to further evaluate the effect of topical application of the composite dressing containing medical glucose syrup on changes in blood glucose levels in diabetic rats, blood glucose levels in the rats of Example 1 group were monitored during treatment, and the test results are shown in Table 4. The average blood glucose level of the rats in Example 1 group at each time point during treatment was 16.8-17.6 mmol / L. The blood glucose level remained relatively stable at each time point, and no trend of continuous increase with the extension of topical application of the composite dressing was observed.
[0152] Table 5 shows a further comparison of the effects of the present invention with those of recently reported wound dressings. As can be seen from Table 5, in a Staphylococcus aureus-infected diabetic rat dorsal full-thickness wound model (10 mm diameter), Example 1 of the present invention achieved a wound healing rate of 98.4% on day 13. The optimal treatment group listed in the table typically achieved a wound healing rate of 92.1%-98.1% on day 14 or 15, indicating that the therapeutic effects of the present invention are close to or even exceed those of some recently reported wound dressings.
[0153] Table 1. XRD phase analysis and nitrogen adsorption-desorption curve test results of Examples 1-3 and Comparative Examples 1-3
[0154]
[0155] It should be noted that the phase composition, BET specific surface area, total pore volume, NLDFT mesopore ratio, and NLDFT micropore ratio in Table 1 are derived from XRD analysis and nitrogen adsorption-desorption analysis, respectively. That is, the XRD phase analysis results are presented as phase composition, and the nitrogen adsorption-desorption curve results are presented as BET specific surface area (m²). 2 The pore volume (mL / g), total pore volume (mL / g), NLDFT mesopore percentage (%), and NLDFT micropore percentage (%) are presented. The phase composition was determined based on the positions of the XRD diffraction peaks of each sample and their matching results with the corresponding standard diffraction cards. The BET surface area was calculated using the BET method based on the nitrogen adsorption-desorption isotherm obtained at 77 K; the total pore volume was calculated based on the nitrogen adsorption-desorption test results; and the mesopore and micropore percentages were calculated based on the nitrogen adsorption-desorption isotherm, using the NLDFT model to analyze the pore size distribution.
[0156] Table 2. Results of vitamin D3 and glycine content determination in Examples 1 and Comparative Examples 1-3
[0157]
[0158] It should be noted that in Table 2, the test results are presented as the mass of vitamin D3 detected (mg), the vitamin D3 mass ratio (wt%), the mass of glycine detected (mg), and the glycine mass ratio (wt%).
[0159] Table 3. Wound healing rate data for Example 1 and Comparative Examples 1-6
[0160]
[0161] Healing rate (%) = [(A0-A 13 [) / A0]×100%, where A0 is the wound area on the day the wound formed (day 0), A 13 The residual wound area was measured on day 13 post-treatment. The wound area was obtained by photographing the wound and performing area analysis using ImageJ software. The healing rates of chronic diabetic foot wounds in rat models of Example 1 and Comparative Examples 1-6 were obtained using the above wound area measurement data and calculation formulas.
[0162] Table 4. Changes in blood glucose levels in rats during treatment in Example 1 group.
[0163]
[0164] Table 5. Comparison of the effects of the composite dressing of the present invention with previously recorded wound dressings.
[0165]
[0166] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A method for preparing a hypertonic composite dressing containing heterojunction nanozymes, characterized in that: Includes the following steps: S.1 After uniformly mixing choline chloride, ethylene glycol, MnCl2·4H2O, poloxamer and hexamethylenetetramine, a solvothermal reaction was carried out, and the resulting precipitate was calcined to obtain the Mn-based precursor. S.2 The Mn-based precursor was ultrasonically dispersed in a solvent, and then Ce(NO3)3·6H2O and NH4HCO3 aqueous solution were added for a water bath reaction. Ascorbic acid was added and the reaction was carried out again in a water bath. The precipitate obtained from the reaction was heat-treated to obtain CeO2 / Mn3O4 nanozyme. S.3 CeO2 / Mn3O4 nanozymes were added to anhydrous ethanol and ultrasonically dispersed to obtain a nanozyme dispersion. Glycine was dissolved in deionized water and vitamin D3 was dissolved in anhydrous ethanol. The two were then mixed and dispersed by shaking to obtain a functional component mixture. This mixture was added dropwise to the CeO2 / Mn3O4 nanozyme dispersion and stirred in the dark. After the reaction was completed, the resulting precipitate was the nanozyme loaded with functional components, which was denoted as intermediate product A. S.4 Intermediate product A was added to a hyaluronic acid solution, and the mixture was stirred in the dark to carry out non-covalent surface adsorption modification. After the reaction was completed, the precipitate obtained was HA@CeO2 / Mn3O4 nanozyme. S.5 Carbomer, medical glucose syrup and HA@CeO2 / Mn3O4 nanozyme were added to deionized water and swollen for 20-28 hours; the pH of the system was adjusted to neutral to obtain HA@CeO2 / Mn3O4 dressing.
2. The preparation method according to claim 1, characterized in that: In step S.1, the conditions for the solvothermal reaction are: temperature 90-115℃, time 5-7h; the conditions for calcination are: heating rate 5℃ / min, calcination temperature 280-330℃, calcination time 2-4h.
3. The preparation method according to claim 1 or 2, characterized in that: In step S.1, the molar ratio of choline chloride to MnCl2·4H2O is 120:2-5; the molar ratio of choline chloride to hexamethylenetetramine is 120:4-7; and 180-230 mg of poloxamer and 20-30 mL of ethylene glycol are added for every 120 mmol of choline chloride.
4. The preparation method according to claim 1, characterized in that: In step S.2, the conditions for the first water bath reaction are: reaction temperature 65-75℃, time 4-6h; the conditions for the second water bath reaction are: reaction temperature 75-85℃, time 0.5-1.5h; the conditions for heat treatment are: nitrogen atmosphere, heating rate 2℃ / min, heat treatment temperature 270-310℃, time 2.5-4h.
5. The preparation method according to claim 1 or 4, characterized in that: In step S.2, 300 mg of Mn-based precursor is used as the quantification standard, Ce(NO3)3·6H2O is 0.4-0.6 mmol, NH4HCO3 is 4-7 mmol, ascorbic acid is 0.9-1.2 mmol, and ethanol / deionized water mixed solvent is 55-70 mL.
6. The preparation method according to claim 1, characterized in that: In step S.3, the mass-to-volume ratio of the CeO2 / Mn3O4 nanozyme to anhydrous ethanol is 300:35-50 mg / mL; the mass-to-volume ratio of the glycine to deionized water is 180-230:25-40 mg / mL; the mass-to-volume ratio of vitamin D3 to anhydrous ethanol is 20-30:15-25 mg / mL; and the mass ratio of the CeO2 / Mn3O4 nanozyme, glycine, and vitamin D3 is 300:180-230:20-30.
7. The preparation method according to claim 1, characterized in that: In step S.4, the mass-to-volume ratio of hyaluronic acid to deionized water is 600-800:25-40 mg / mL; the mass ratio of intermediate product A to hyaluronic acid is 300:600-800.
8. The preparation method according to claim 1, characterized in that: In step S.5, the mass ratio of carbomer, medical glucose syrup, and HA@CeO2 / Mn3O4 nanozyme is 1:35-55:0.45-0.6, and the mass-to-volume ratio of carbomer to deionized water is 1:120-180 g / mL.
9. A hyperpermeable composite dressing containing heterojunction nanozymes prepared by the preparation method according to any one of claims 1-8, characterized in that: The composite dressing includes carbomer, medical glucose syrup, and HA@CeO2 / Mn3O4 nanozyme.
10. The use of a hypertonic composite dressing containing heterojunction nanozymes prepared by the preparation method according to any one of claims 1-8 in the preparation of a drug for treating chronic diabetic foot wounds.
